Lights out : a movement to help migrating birds - Stremer, Jessica (A Paula Wiseman Book, Simon & Schuster Books for Young Readers, 2024)
"Based on the real-life Lights Out movement, this inspirational story shows how people can combat light pollution and make a big difference in helping to save migrating birds by turning lights off at night."--